Pathophysiology, Diagnosis and Treatment of Immune Thrombocytopenia - Mihnea-Alexandru Găman; Amelia Maria Găman (International Journal of Medical Students, 2017)
Immune thrombocytopenia (ITP) is an acquired disorder characterized by isolated thrombocytopenia with a peripheral blood count < 100.000/ mm3 in the absence of any obvious initiating or underlying causes, by antibody mediated destruction of platelets and suppression of megakaryocyte and platelet production on the basis of immune deregulation. ITP is idiopathic (primary) in 80% of cases and secondary to several associated disorders in 20% of cases. A diagnosis of exclusion, based on patient history, physical examination, complete blood count and examination of the peripheral blood smear, is used for ITP. The treatment of ITP is indicated in adult patients with platelet counts below 20.000-30.000/ mm3, with bleedings or risk for bleeding. First line therapy is represented by corticosteroids, intravenous immunoglobulins and intravenous anti-RhD. Second-line treatment is represented by: splenectomy, inhibition of the monocytic phagocytic system therapy, immunosupressive therapy, anabolic steroids, anti-CD20 therapy, and thrombopoietin receptor agonists.